2019
DOI: 10.1038/s41598-019-52961-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Matricellular Protein Expression Signatures in Mechanistically Diverse Mouse Models of Kidney Injury

Abstract: Fibrosis is the most common pathophysiological manifestation of Chronic Kidney Disease (CKD). It is defined as excessive deposition of extracellular matrix (ECM) proteins. Embedded within the ECM are a family of proteins called Matricellular Proteins (MCPs), which are typically expressed during chronic pathologies for ECM processing. As such, identifying potential MCPs in the pathological secretome of a damaged kidney could serve as diagnostic/therapeutic targets of fibrosis. Using published RNA-Seq data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…In a meta-analysis study of rat glomerular transcriptome profiling, it was confirmed that GM2A was highly expressed in various diabetic kidney disease rat [ 49 ]. Through the mouse kidney injury model experiment, SPARCL1 showed that mRNA expression was not changed in the acute phase, but the expression level was high in the fibrosis of the kidney [ 50 ], and it inhibited the movement and invasion of renal cell carcinoma [ 51 ]. Lastly, ACP 2, one of the lysosomal enzymes, is a protein used in peptiduria [ 52 ] or lysosomal enzymuria [ 53 ] that measures kidney disease in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis study of rat glomerular transcriptome profiling, it was confirmed that GM2A was highly expressed in various diabetic kidney disease rat [ 49 ]. Through the mouse kidney injury model experiment, SPARCL1 showed that mRNA expression was not changed in the acute phase, but the expression level was high in the fibrosis of the kidney [ 50 ], and it inhibited the movement and invasion of renal cell carcinoma [ 51 ]. Lastly, ACP 2, one of the lysosomal enzymes, is a protein used in peptiduria [ 52 ] or lysosomal enzymuria [ 53 ] that measures kidney disease in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, there is still much to be discovered regarding the exquisite spatiotemporal regulation of MCP expression patterns and functions in the extracellular space during cancer tissue remodeling, similar to the approach taken in fibrosis (17). In this respect, as more and more knowledge accumulates, it should be possible to design appropriate clinical studies that could firmly establish MCPs as useful biomarkers and therapeutic targets in cancer.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…These proteins are primarily implicated in bone morphogenesis and biomineralization, and were thus thought to be exclusively localized to mineralized tissue such as bone and teeth (16). However, apart from these traditional functions, SIBLING members were also shown to influence cellular proliferation/survival pathways, collagen fibrillogenesis, MMP activities and response to injury (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…As a matricellular protein, OPN is the first mediator associated with ECM degeneration, which stimulates the release of the local fibrogenic mediators and promotes the tissue's failure. In renal inflammation and fibrosis, matricellular OPN is involved in macrophages and T-cell recruitment, contributing to propagate ECM deposition signaling [54,55]. Under chronic renal flow overload, angiotensin II upregulates transforming growth factor β (TGF-β) as well all the mediators associated with ECM turnover, including OPN [14].…”
Section: Opn As a Matricellular Protein In Fat Cardiac And Renal Tismentioning
confidence: 99%